Service-Learning for Post-Disaster Community Recovery: A Community Empowerment Program in Rancong Village, Aceh, Indonesia - Rahmat Fadhil; Raida Agustina; Hendra Halim; Jalaluddin; Meutia Dwi Novita Sari; Dini Hadhirah (Jurnal Pengabdian Bakti Akademisi, 2026)
This community service article reports a post-disaster recovery program conducted in Rancong Village, Kuta Blang District, Bireuen Regency, Aceh, following a hydrometeorological flood that disrupted clean water access, environmental sanitation, public facilities, and children’s psychosocial well-being. The program aimed to support community recovery through an integrated and participatory approach. The activity was implemented for 20 days, from 2 to 21 February 2026, involving university students, field supervisors, village authorities, and local residents through a service-learning method. The main intervention focused on installing a clean water filtration system, while supporting activities included cleaning flood-affected houses, restoring religious and public facilities, clearing drainage channels and roads, introducing a low-smoke rocket stove for household waste management, and conducting educational and recreational activities for children. The results show that the program improved access to cleaner water, restored environmental and communal functions, strengthened community participation, and created a more positive post-disaster social atmosphere.